Treasures of Integral Medicine Between Islam and Local Bugis Bone Medicine in the Lontara Manuscript - Ruslan Sangaji; Nirwana Rasyid (IBDA` : Jurnal Kajian Islam dan Budaya, 2022)
This study aims to determine the Islamic medicine dimension which is integrated with the local medicine. The dimensions are impor- tant to hnow because they are parts of the human health sciences that are useful for the present. The data come from the lontara manuscriptof Inhoud Lontara’ No. 125 which contains 23 types of diseases and their treatment. This study uses a philological and anthropological approach. The findings illustrate that there are two medicine dimensions. Those are the medicine dimensions through gau-gauheng, and the medicine dimensions related to taneng-taneng pabbura. However, hnowledge of local medicine related to gau-gauheng is more lihely to be integrated with Islamic medicine. The term gau-gauheng refers to the meaning of “certain treatments”. Meanwhile, the term taneng-taneng pabbura refers to the meaning of “plants containing medical elements”. The integration of Islamic culture in the local Bugis culture is strongly influenced by the Islamization process in Bone. The identity of each culture continues to transform so cultural acculturation occurs. Thus, the integration of medical science shows the efforts of the Bugis people in Bone to treat and main- tain human health. The two concepts have complemented each other and have gone hand in hand for a long time before health and medical science progressed and developed today. Various information in the Bugis lontara manuscripthas carried the basics of natural care and treatment and has contributed to the realization of human health.